Complete mitochondrial genome of chestnut-fronted macaw (Ara severus, Psittaciformes). Issue 1 (1st January 2017) - Urantówka, Adam Dawid; Kroczak, Aleksandra; Mackiewicz, Paweł
Abstract: Six genera from Arini tribe form a morphologically diverse group named macaws, which differ from other Arini in the presence of bare facial area. Macaws are further distinguished by the bare face pattern, plumage colouration and body size. Six of the eight macaw species from Ara genus can be easily segregated into three pairs according to their colouration. An exception is Ara severus, which differs from others in their size and morphology. The lack of appropriate molecular markers precludes determination of its phylogenetic position. Therefore, the mitogenome of Ara severus presented in this report will be indispensable to refine these phylogenetic relationships.